Screening symptoms of reactive attachment disorder: evidence for measurement invariance and convergent validity. Issue 3 (11th September 2013) - Vervoort, Eleonora; De Schipper, J. Clasien; Bosmans, Guy; Verschueren, Karine
Abstract The Relationship Problems Questionnaire (RPQ) was developed to screen symptoms of the inhibited and disinhibited subtype of reactive attachment disorder (RAD). This study further examines the psychometric properties of the RPQ in children with severe emotional and behavioural problems by testing its measurement invariance across informants and its convergent validity. Parents and teachers of 152 children [mean age (Mage) = 7.92] from 20 schools for special education filled out the RPQ and the Strengths and Difficulties Questionnaire (SDQ). During a home visit in a subsample of 77 children the Disturbances of Attachment Interview (DAI) was administered to the caregiver and the child was observed using an observational schedule for RAD. Exploratory and confirmatory factor analyses revealed the expected two‐factor structure for both parent and teacher RPQ. Configural and metric invariance, but no scalar invariance, were obtained across informants. Both RPQ‐subscales had acceptable to good internal consistencies and correlated as expected with similar DAI‐subscales. Furthermore, the disinhibited RPQ‐scale related with observations of the child's approach to a stranger. Finally, significant associations were found between the RPQ and the SDQ. Overall, the RPQ has good psychometric qualities as a multi‐informant instrument for RAD‐symptoms in children with severe emotional and behavioural problems. Copyright © 2013 John Wiley & Sons, Ltd.